Conviver com verdades penúltimas? Um percurso kantiano - Pirni, Alberto (Studia Kantiana, 2014)
O presente artigo pretende oferecer uma interpretação do tema da verdade (entendida como busca de sentido) no pensamento de Kant, procurando desconstruir um nexo que a história dos conceitos deu como óbvio e imutável, a saber, o nexo entre verdade e ultimidade. Ao fazer isso, pretende-se percorrer duas diferentes ramificações de tal nexo: uma entre último e estável e outra entre último e instável (§ 1). Em conformidade com a epoché, que Kant recomenda com respeito ao "reino da verdade última", efetuaremos um excursus sobre o "reino da penultimidade" e sobre o correspondente nexo duplo entre penúltimo e estável - considerado a partir da reflexão de Hegel - por um lado e entre penúltimo e instável - considerado a partir da perspectiva habermasiana - pelo outro (§ 2). Contudo, parece interessante entender como Kant delineia sua reflexão sobre o tema da verdade na Crítica da razão pura (§ 3), mas também entender quais são os limites da possibilidade de prolongar o "discurso sobre a verdade" além da Analítica, ou seja, no interior da Dialética transcendental, em sentido lógico e ontológico (§§ 4 e 5). Este percurso, ao tentar uma releitura da dialética entre ideia e ideal, proporá como conclusão um novo olhar sobre a dialética entre último e penúltimo (§ 6), na busca de uma "terceira via" entre estável e instável, ou seja, de uma renovada lógica da pluralidade capaz de legitimar o engajamento moral de todo e qualquer agente moral visando a convivência com qualquer ser capaz de razão. <!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Abstract: The essay focuses on the concept of truth - as search for meaning - within the Kant's perspective, by seeking for deconstructing a link - between truth and ultimacy - that the western history of ideas has always assumed as consolidated and not modifiable. In doing that, the essay concentrates first on two different ramifications of such a link: the ramification between ultimate and stable, on the one hand, and that one between ultimate and unstable, on the other (§ 1). According to the epoché suggested by Kant about the "realm of ultimate truth", then the essay deals with an excursus about the "realm of penultimate" and about the corresponding dual link: that one between penultimate and stable - here explored through the concept of law by Hegel - and the second one between the penultimate and unstable - following the concept of public sphere by Habermas (§ 2). However, it seems interesting to understand how Kant precisely outlines his reflection on the topic of truth in the Critique of Pure Reason (§ 3). But it's also of particular interest to understand possibilities and limits of extending the "discourse of truth", by referring to its logical and ontological meaning, beyond the Transcendental Analytic, ie within the Transcendental Dialectic (§§ 4-5). Conclusively, this argumentative path would like to offer a new perspective about the dialectic between ultimate and penultimate by trying to re-read the Kantian conceptual dialectic between idea and ideal (§ 6). The main goal of such a re-reading is the search for a "third way" between stable and unstable, i.e., a renewed "logic of plurality" able of legitimizing the moral commitment of any rational agent who, according to the law of reason, tries to make effective the attempt of living together with any other. Keywords: truth, ultimate, penultimate, Critique of Pure Reason, idea, ideal, Kant, Hegel, Habermas <!--[if gte mso 9]> <![endif]-->